Islamicate Secularities: New Perspectives on a Contested Concept - Dreßler, Markus (Historical social research, 2019)
In the colonial era, new distinctions and differentiations between religious and non-religious spheres took shape within inner-Islamic discourses, partly as a product of encounters with Western knowledge. This introduction conceptualizes these distinctions and differentiations in relation to Islam, drawing on Marshall Hodgson’s concept of the Islamicate, which we employ for our heuristic notion of Islamicate secularities. It charts the paradigmatic conflicts that shape the contested fields of Islamic and secularity/secularism studies. The introduction discusses the epistemological and political context of these debates, and argues that theoretical and normative conflicts should not hinder further empirical inquiries into forms of secularity in Islamicate contexts. It also explores promising theoretical and methodological approaches for further explorations. Particular emphasis is laid on the historical trajectories and conditions, close in time or distant, that have played a role in the formation of contemporary Islamicate secularities.